Utilizing seaweeds for food production and applications: A comprehensive review of Kappaphycus Alvarezii - Hasmadi Mamat; Ahmad Hazim Abdul Aziz; Mohd Khairi Zainol; Wolyna Pindi; Norazlina Mohammad Ridhwan; Rovina Kobun; Nicky Rahmana Putra (Taylor & Francis Online, 2024)
This review explores the versatility of K. alvarezii in various food applications, including bakery, meat, snacks, jams, and prebiotics. Abundant in vitamins, minerals, antioxidants, and bioactives, seaweed enhances texture, reduces fat, and provides nutritional benefits. In meat products, seaweed acts as a gelling and binding agent, improving texture, moisture retention, and allowing for salt and fat reduction. Seaweed snacks offer both health benefits and a pleasant aroma, while K. alvarezii’s prebiotics support gut health by promoting beneficial bacteria. Additionally, seaweed serves as a natural gelling agent, stabilizing jam and jelly textures, and exhibits promise in sustainable food packaging through edible films.